Analisis Implementasi Pembelajaran Deep Learning pada Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Ramadhan, Diky; Purnomo, Heru (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
Education holds a significant role in shaping human resources that are not only of high quality but also capable of competing globally. It is not limited to the transfer of knowledge; education also fosters moral values, character development, and critical thinking skills, which are essential in navigating the complexities of the modern world. However, learning at the elementary level still encounters several challenges, particularly in developing students’ critical thinking abilities. Many students face difficulties in identifying problems, constructing logical reasoning, making conclusions, and actively participating in discussions or solving problems. To overcome these obstacles, the deep learning approach has been introduced as a relevant solution. This method focuses on building meaningful understanding by connecting learning content with real-life contexts, while encouraging reflective and analytical thinking. This study aims to describe the implementation of deep learning in Science and Social Studies (IPAS) learning for fifth-grade students at SD Negeri Gedongkuning. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation. The results show that students became more active and demonstrated better critical thinking skills. Nevertheless, several barriers remain, such as limited instructional time, inadequate facilities, and teacher readiness. Therefore, strong policy support, regular teacher training, and parental involvement are crucial for successful implementation.